Anonymous hierarchical identity-based encryption without key delegation in decryption. (2015) - Luo, Song
Hierarchical identity-based encryption (HIBE) introduces the concept of hierarchical identity in identity-based encryption (IBE) which eases the burden of key generation centre. Anonymous identity-based encryption is another extension of IBE in which the ciphertext leaks no information about the target identity. In this paper, we propose a new anonymous hierarchical identity-based encryption system. Unlike previous anonymous HIBE system, our system needs no key delegation in decryption, i.e., the user can decrypt the ciphertext directly if his identity vector is the prefix of the target identity vector. So it is not necessary for the user to know the target identity vector, which enhances the practicality of anonymous HIBE systems. Our system is constructed in composite order groups and proven adaptive security and anonymity from four static assumptions by using the dual system encryption technique.